Ultrasound guided L5–S1 placement of labor epidural does not improve dermatomal block in parturients. (May 2019) - Malik, T.; Malas, O.; Thompson, A.
Highlights: An epidural catheter at L5–S1 results in similar S2 coverage to one at L2–4. Quality of labor analgesia is similar whether catheter is placed at L5–S1 or L3-4. Ultrasound-guided placement is as effective as using skin landmarks. Abstract: Background: Based on their experience or training, anesthesiologists typically use the iliac crest as a landmark to choose the L3-4 or L2-3 interspace for labor epidural catheter placement. There is no evidence-based recommendation to guide the exact placement. We hypothesized that lower placement of the catheter would lead to a higher incidence of S2 dermatomal block and improved analgesia in late labor and at delivery. Methods: One-hundred parturients requesting epidural analgesia were randomly assigned to receive ultrasound-guided L5–S1 epidural catheter placement (experimental group) or non-ultrasound-guided higher lumbar interspace placement (control group). The primary outcome was the incidence of S2 block 30 minutes after administering 10 mL 0.125% bupivacaine. Secondary outcomes were average pain throughout labor and maximum pain during labor or during delivery. Results: Forty-nine subjects were enrolled in control group and 47 in the experimental group. The primary endpoint did not significantly differ between groups (control group 81% vs experimental group 91%, P =0.24). The secondary endpoints were not significantly different: pain relief after 30 minutes (mean pain score 1.4 in the control group vs 1.9 in the experimental group, P =0.2) and pain at delivery (mean score 4 in the control group vs 3.9 in the experimental group, P =0.6). Conclusion: Placement of an epidural catheter at the L5–S1 interspace using ultrasound did not improve sacral sensory block coverage when compared with an epidural catheter placed at a higher lumbar interspace, without using ultrasound guidance.